HUBUNGAN USIA, PARITAS DAN PEKER HUBUNGAN USIA, PARITAS DAN PEKERJAAN TERHADAP KEJADIAN ANEMIA PADA IBU HAMIL - Yuni Subhi Isnaini; Riska Yuliaprida; Priscilla Jessica Pihahey (Jurusan Keperawatan Poltekkes Kemenkes Sorong, 2021)
ABSTRACT Anemia is a condition in which the body has too few red blood cells, which contain hemoglobin, which carries oxygen to all body tissues. According to (WHO, 2017), globally the prevalence of anemia in pregnant women worldwide is 41.8%. The purpose of the study was to determine the relationship between age, parity and occupation of the incidence of anemia in pregnant women at the Sowi Health Center. The research design is a cross sectional study where the research is measured and data are collected at the same time to study the relationship between variables and certain variables. The research sample is a saturated sample (total sampling) from the population taken as a data source where the research sample consists of all anemic pregnant women at the Sowi Health Center. The results showed that there was no relationship between age, parity and occupation on the incidence of anemia in pregnant women at the Sowi Health Center. The results of the analysis of maternal age data showed p value = 0.605 > 0.05. For the results of the analysis of maternal parity data, the p value = 0.570 > 0.05 and for the results of the analysis of the mother's work data, the p value = 0.089 > 0.05. Keywords: Age, Parity,Profession,Anemia In Pregnant Women